Analysis of Administrative Management in Costa Rican Educational Institutions: Perceptions of Teachers and Principals - Cerdas Montano, Vriginia (2017)
Educational institutions, as complex and dynamic organizations, are characterized by the social processes that lead them to the accomplishment of goals and common objectives. Regarding this matter, administrative management has the challenge of favoring pertinent alternatives for every context offering answers to the necessities and interests of the educational community and, at the same time, of being responsive for the administrative structure of the system of which it is a part. This study has the objective of analyzing both the teaching staff and the management´s perception about administrative management. The methodology used for the accomplishment of the objectives arises from a mixed approach, specifically from a quantitative perspective through a non-experimental transversal design, while the qualitative approach is based on a phenomenological method. Data recollection was done whit an ad hoc questionnaire applied to 192 teachers and semi structured interviews conducted to six Costa Rican public school managers. Results show that there is some lake of knowledge by the teaching staff on the functions inherent in the administrative management; likewise, there are relevant aspects regarding the guidelines emanated from the Ministry of Public Education in response to the needs of the context, infrastructure and economic resources destined by the Costa Rican State as means to support teaching as well as teachers participation in the school activities.